Digital Marketing Assistance for Coconut Products to Improve the Economy of Village Communities - Suib, Mohammad Syaiful; Yulianti; Shaleha, Siti Hajar; Laila, Ratih Ika Wulan Dari; Mutiara, Nur; Lestari, Angel Mareta Eka Ayu (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2024)
This report discusses the Digital Marketing Strategy for Coconut Production to Improve the Community Economy in Sentul Village, Gading District, Probolinggo Regency, East Java, in increasing sales volume through e-commerce platforms. This assistance aims to increase knowledge and skills in Sentul Village in managing coconut production, digital marketing strategies and online sales. The assistance method used is training and direct assistance in managing coconut production through digital marketing. The results of the mentoring show a significant increase in digital marketing strategies for coconut production in Sentul village after participating in the mentoring program. This increase is attributed to increased knowledge and skills in Sentuk Village in coconut production, digital marketing strategies and online sales.